Islamic Counseling Guidance Mujadalah Technique for Child Victims of Psychological Violence - Majdi, M. Zuhdi Zainul; Suryadi, Iwan Eka; Hadi, Syamsul (Grief and Trauma, 2024)
Violence is an act committed by someone or a number of people who are in a strong position (feel strong) to someone or some people who are in a weak position (seen as weak/weakened), both physically and non-physically. The purpose of the study is how the Islamic counseling guidance mujadalah technique is effective in increasing understanding and awareness of child victims of psychological violence. Research using qualitative with case study method. The subjects used in the study were client "X" and Social Workers at the East Lombok Children's Social Rehabilitation Center totaling 3 people. The research tools used are observation, interviews, and documentation. The results showed that Islamic counseling guidance with mujadalah techniques was effective in increasing resilience in children who were victims of psychological violence but needed to be further improved so that there were no mental and physical disturbances in facing challenges and obstacles in the future.